Stochastic Model for Safety and Qaulity Management in the Pacific Oyster Supply Chain - Fernandez Piquer, J; John Bowman; Thomas Ross; Estrada-Flores, S; Mark Tamplin (2011)
Vibrio parahaemolyticus is a naturally occurring bacterium in seawater and some strains can cause human disease. V. parahaemolyticus can accumulate and grow in oysters stored at elevated temperatures, representing a potential food safety risk. Moreover, high temperatures during oyster storage will enhance the growth of the overall bacteria composition affecting oyster shelf-life.